2008
DOI: 10.1017/s1754470x08000032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pain-related fear in chronic (persistent) pain: the role of safety-seeking behaviour and imagery

Abstract: It is widely recognized that psychological factors play a central role in the adjustment process and subsequent management of chronic pain. The role of anxiety, and specifically pain-related fear, has received particular attention. Paralleling developments in the anxiety disorders literature, psychological models of pain-related fear now highlight the importance of cognitive processes in its maintenance and treatment. However, theoretical and treatment advances in the anxiety disorders literature have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Other studies have documented the importance of identifying individual-level coping mechanisms (Davis et al, 2004;Gatchel et al, 2007). For example, recent research has verified the moderating properties of spirituality (Wachholtz et al, 2007), self-efficacy (Cannella et al, 2007), emotional intelligence (Saklofske et al, 2007), cognitive control (Paez-Blarrina et al, 2008) and safety seeking propensity (Jamani and Clyde, 2008) in this research domain.…”
Section: Jmp 247 584mentioning
confidence: 89%
“…Other studies have documented the importance of identifying individual-level coping mechanisms (Davis et al, 2004;Gatchel et al, 2007). For example, recent research has verified the moderating properties of spirituality (Wachholtz et al, 2007), self-efficacy (Cannella et al, 2007), emotional intelligence (Saklofske et al, 2007), cognitive control (Paez-Blarrina et al, 2008) and safety seeking propensity (Jamani and Clyde, 2008) in this research domain.…”
Section: Jmp 247 584mentioning
confidence: 89%
“…The communal coping model of pain (Sullivan, 2012) states that catastrophizing is a form of interpersonal communication used to cope with pain, motivated by proximity or support-seeking, and to solicit empathic responses. However, catastrophizing is a significant predictor of pain behaviour (Thibault, Loisel, Durand, & Sullivan, 2008), and it is suggested that metaphor use may be a form of catastrophizing (Jamani & Clyde, 2008), causing the sufferer to pay increased attention to the pain. Such language use may increase the risk of negative emotional states and hypervigilance (Holmes et al, 2007;Villemure & Bushnell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Enriched understanding, therefore, may be reached by returning to the original transcripts with a focus on rates of metaphor use and functions of such language. This can provide a foundation for evidence‐based integration of imagery‐based interventions with cognitive‐behavioural techniques (Jamani & Clyde, ).…”
Section: Introductionmentioning
confidence: 99%
“…Images of people in pain (pain sufferers) have received scant interest, despite the recognition over 50 years ago of the influence of cognitive factors on pain experience (Melzack and Wall, 1965). Images experienced by pain sufferers have been reported by clinicians (Winterowd, Beck and Greuner, 2003;Jamani and Clyde, 2008) and researchers (Potter, 2007;Gillanders, Potter and Morris, in press;Philips, 2011;Berna et al, 2011). However, the effect of distressing imagery upon the pain experience, and the systematic modification of images in pain management programs has not been addressed.…”
Section: Introductionmentioning
confidence: 99%